The purse-seine fishery for small pelagic fishes off the Madeira Archipelago. Issue 4 (17th December 2019) - Tejerina, R; Hermida, M; Faria, G; Delgado, J
Abstract : Small pelagic fishes constitute a valuable food resource for human consumption and are also important components of marine food webs. At Madeira, a Portuguese archipelago in the eastern Atlantic, they are the target of a year-round purse-seine fishery operating mainly off the south coast of Madeira Island. Landings of this fishery are mostly composed of blue jack mackerel Trachurus picturatus, Atlantic chub mackerel Scomber colias, and small amounts of sardine Sardina pilchardus . A fisheries observation programme was carried out, from October 2016 to December 2017, to quantify discards and slipping. Large differences were detected in the proportion of each species present in the landings and in the gross catches. Large amounts of the caught S. pilchardus (76.6%), S. colias (42.6%) and even T. picturatus (14.2%) were either discarded dead or slipped. Reasons for discarding included small sizes and a low market value obtained in the first sale of these species. The fishing pattern in this region is in striking contrast with that for mainland Portugal, where S. pilchardus is the most valuable small pelagic species, fetching a high market price. The results of this study suggest a need for the introduction of specific measures to promote more effective utilisation of the resources.